THE PROFILE OF FRACTURE IN PATIENTS UNDER 17 YEARS OF AGE AT RSUD DR SOETOMO IN THE PERIOD OF 2013-2014 - Satria Nur Sya'ban; Widati Fatmaningrum; Sulis Bayusentono (Journal Orthopaedi and Traumatology Surabaya, 2017)
Fractures in children are important problem nowadays. Governmental census lists people under 17 years old as the largest contributor to fracture cases in Indonesia. The rapid increase in motor vehicle use, a hallmark of economic growth in developing countries, led to sharp increase in road saturation and consequently, rise in traffic related injuries. Variables involved in pediatric fractures needs to be identified and mapped to provide basis for the creation of better preventive measures to reduce problem before it happens. Thus, the purpose of this research is to create a profile of fracture in patients under the age of 17 years’ old at RSUD Dr Soetomo. The research is descriptive study which is performed by analyzing medical records in RSUD Dr Soetomo against the following: Age, Sex, Type of fracture, Cause of fracture, Time of fracture, Location of fracture, and Duration between admission and treatment. Data is then tabulated and converted into a bar graph for easier analysis. The research found that fractures in children most commonly occur at the 10-14 years’ age group (41.8%), happens more frequently in boys than in girls (69.5%), is dominated by closed fractures over open fractures (75.9%), and is most often caused by traffic accidents (60.9%). Consequently, the location in which fractures are most prevalent is the “street” (63.1%). It is also found that the highest incidence of fractures cases happens within the 12.01-18.00 time-span (19.1%) and is treated within the first 8 hours of admission to the hospital (79.4%).